PENGARUH PENYULUHAN TENTANG HIV/AIDS TERHADAP PENGETAHUAN DAN SIKAP SISWA DI SMA NEGERI 1 MANADO - Ayuningsih, Niasari; Rondonuwu, Rolly; Mulyadi, Ns (Universitas Sam Ratulangi, 2014)
Abstract: The incidence of HIV/AIDS continues to increase every year. In North Sulawesi, the data of KPA in February 2013 for the 15-19 year age range, there are 33 people living with HIV and AIDS. Aim to determine the effect of counseling on HIV/AIDS knowledge and attitudes towards students in SMA 1 Manado. This research method Pre-Experimental Designs with one group pre-post test, a population of 90 people were taken by purposive sampling method samples obtained 54 respondents with a number of people with primary data collection method of filling the questionnaire through knowledge and attitudes. The data collected by questionnaire. The results show respondents knowledgeable counseling both before 13.0% and after 75.9% extension. Respondents who behave well before counseling was 5.6% whereas after counseling was 68.5%. Conclusion extension affects students' knowledge and attitudes about HIV / AIDS (P = 0.000). Suggestion expected the students more active and thorough in seeking information from a variety of media that exist, so that the students have a high knowledge and understanding about HIV / AIDS in order to avoid the risks of HIV / AIDS. Keywords : HIV/AIDS, knowledge, attitude Abstrak: Angka kejadian HIV/AIDS terus meningkat setiap tahunnya. Di Sulawesi Utara, data dari KPA pada Februari 2013 untuk rentang umur 15-19 tahun terdapat 33 penderita HIV dan AIDS. Tujuan untuk mengetahui pengaruh penyuluhan tentang HIV/AIDS terhadap pengetahuan dan sikap siswa di SMA Negeri 1 Manado. Metode penelitian ini Pra-Eksperimental dengan Desain one group pre-post test, populasi sebanyak 90 orang diambil sampel dengan metode purposive sampling didapatkan responden dengan jumlah 54 orang dengan metode pengambilan data primer melalui pengisian kuisioner pengetahuan dan sikap. Cara pengumpulan data dengan metode kuesioner. Hasil penelitian menunjukkan responden berpengetahuan baik sebelum dilakukan penyuluhan 13,0% dan sesudah dilakukan penyuluhan 75,9%. Responden yang bersikap baik sebelum dilakukan penyuluhan 5,6% sedangkan sesudah dilakukan penyuluhan 68,5%. Kesimpulan penyuluhan mempengaruhi pengetahuan dan sikap siswa tentang HIV/AIDS dengan (nilai P=0,000). Saran diharapkan para siswa lebih aktif dan menyeluruh dalam mencari informasi dari berbagai media yang ada, sehingga para siswa memiliki wawasan dan pemahaman yang tinggi tentang HIV/AIDS agar terhindar dari resiko-resiko terjadinya HIV/AIDS. Kata kunci: HIV/AIDS, pengetahuan, sikap